NAVIGATING THE DIGITAL SHIFT: DIGITALIZATION ON INTERNSHIP PROGRAMS OF PT PAL INDONESIA - Aji, Gagas Gayuh; Hanifah, Afifah Hidayatul (Sharia Business Management UIN Raden Intan Lampung, 2023)
This research assessed OJT Digitalization Systems' effectiveness in improving the OJT process's efficiency at PT PAL Indonesia. A qualitative approach with a case study design was employed, involving interviews with HR staff, trainers, and participants, alongside process observation. Content analysis was conducted to analyze the collected data. The findings demonstrated that the OJT Digitalization Systems effectively enhanced the efficiency of the OJT process at PT PAL Indonesia. These systems reduced time and cost, improving accessibility and user-friendliness for stakeholders. Furthermore, they enhanced data accuracy during OJT. This research contributes to the existing literature on digitalization in HR practices by providing evidence of the efficiency-boosting potential of OJT Digitalization Systems. It emphasizes the importance of considering stakeholder requirements in digitalization projects. Managers should consider implementing these systems to enhance OJT efficiency and data accuracy, aiding decision-making in HR practices. Policymakers should encourage digitalization adoption in HR to improve workforce development programs. In summary, this research highlights the positive impact of OJT Digitalization Systems on the OJT process, advocating for their implementation to enhance HR practices.